Law librarianship in the twenty-first century - Balleste, Roy; Luna-Lamas, Sonia; Smith-Butler, Lisa (The Scarecrow Press, Incorporated, 2014)
Law Librarianship in the 21st Century, a text for library and information science courses on law librarianship, introduces students to the rapidly evolving world of law librarianship. With no prior knowledge of the law required, students using this book will find practical answers to such questions as: What is law librarianship? How do you become a law librarian? How does law librarianship interrelate with the legal world? Individual chapters provide a concise treatment of such specialized topics as the history of law librarianship, international law, and government documents. Standard topics.